Interfacial phenomena and colloid stability. Volume 2 : Industrial Applications - Tadros, Tharwat F., 1937- (Interfacial Phenomena and Colloid Stability, 2015)
This volume providesthe knowledge that is essential for thecomposition of the complex multi-phase systems used varied areas of application. It enables the physical and formulation chemist as well as the chemical engineer in designing the formulation on the basis of a rational approach, and the formulation scientist to better understanding the factors responsible for producing a stableproduct with optimum application conditions.